Voting - McLean, I (Oxford University Press, 2019)
Dodgson became interested in methods of voting while becoming involved with college appointments, and became one of its most celebrated experts, following in the footsteps of Condorcet and Borda. Critical of standard methods of voting such as first-past-the-post, single-transferable-vote, etc., he presented examples to show their weaknesses. He also proposed a system of proportional representation, and communicated this to newspapers and to Parliamentarians of the time. His Principles of Parliamentary Representation discusses the assignment of seats to multi-member districts and to parties within each district to parties. It is only recently that his contributions to the theory of voting have been recognized.